High prevalence of the liver fluke Amphimerus sp. in domestic cats and dogs in an area for human amphimeriasis in Ecuador. - Manuel Calvopiña; William Cevallos; Richard Atherton; Matthew Saunders; Alexander Small; Hideo Kumazawa; Hiromu Sugiyama (Public Library of Science (PLoS), 2015)
BACKGROUND:Amphimerus sp. is a liver fluke which recently has been shown to have a high prevalence of infection among an indigenous group, Chachi, who reside in a tropical rainforest in the northwestern region of Ecuador. Since it is unknown which animals can act as a reservoir and/or definitive hosts for Amphimerus sp. in this endemic area, a study was done to determine the prevalence of infection in domestic cats and dogs. This information is important to understand the epidemiology, life cycle and control of this parasite. METHODOLOGY/FINDINGS:In July 2012, three Chachi communities located on Rio Cayapas, province of Esmeraldas, were surveyed. A total of 89 of the 109 registered households participated in the study. Of the 27 cats and 43 dogs found residing in the communities, stool samples were collected from 14 cats and 31 dogs (total of 45 animals) and examined microscopically for the presence of Amphimerus eggs. The prevalence of infection was 71.4% in cats and 38.7% in dogs, with similar rates of infection in all three communities. Significantly more cats were infected than dogs (p = 0.042). CONCLUSIONS/SIGNIFICANCE:The data show a high rate of Amphimerus sp. infection in domestic cats and dogs residing in Chachi communities. It can be concluded that these animals act as definitive and reservoir hosts for this liver fluke and that amphimeriasis is a zoonotic disease. These findings provide important epidemiological data which will aid in the development and implementation of control strategies against the transmission of Amphimerus.